The Pharmacodynamic Impact of Apremilast, an Oral Phosphodiesterase 4 Inhibitor, on Circulating Levels of Inflammatory Biomarkers in Patients with Psoriatic Arthritis: Substudy Results from a Phase III, Randomized, Placebo-Controlled Trial (PALACE 1) - Peter H. Schafer; Peng Chen; Lorraine Fang; Andrew Wang; Rajesh Chopra (Journal of Immunology Research)
Apremilast, an oral phosphodiesterase 4 inhibitor, demonstrated effectiveness (versus placebo) for treatment of active psoriatic arthritis in the psoriatic arthritis long-term assessment of clinical efficacy (PALACE) phase III clinical trial program. Pharmacodynamic effects of apremilast on plasma biomarkers associated with inflammation were evaluated in a PALACE 1 substudy. Of 504 patients randomized in PALACE 1, 150 (placebo: n=51; apremilast 20 mg BID: n=51; apremilast 30 mg BID: n=48) provided peripheral blood plasma samples for analysis in a multiplexed cytometric bead array assay measuring 47 proteins associated with systemic inflammatory immune responses. Association between biomarker levels and achievement of 20% improvement from baseline in modified American College of Rheumatology (ACR20) response criteria was assessed by logistic regression. At Week 24, IL-8, TNF-α, IL-6, MIP-1β, MCP-1, and ferritin were significantly reduced from baseline with apremilast 20 mg BID or 30 mg BID versus placebo. ACR20 response correlated with change in TNF-α level with both apremilast doses. At Week 40, IL-17, IL-23, IL-6, and ferritin were significantly decreased and IL-10 and IL-1 receptor antagonists significantly increased with apremilast 30 mg BID versus placebo. In patients with active psoriatic arthritis, apremilast reduced circulating levels of Th1 and Th17 proinflammatory mediators and increased anti-inflammatory mediators.